SCHOOL CONFLICT MEDIATION (Isagoge - Journal of Humanities and Social Sciences, 2021)
The present paper deals with conflict mediation in the school context to defend its importance in promoting peaceful dialogue among students, teachers, and staff of a school. Mediation in the school context reduces violence and allows the integration and reflection of families and the entire community. It seeks to raise awareness about the value of dialogue and peaceful coexistence among the participants of the educational process. Conflict resolution is dealt with from different points of view, in different ways, culturally significant, by a variety of processes, practices, and skills that help prevent, manage in a constructive way, peacefully resolving individual, interpersonal, and institutional conflict.
Keywords: Conflict mediation; Dialogue; School